Effect of irrigation regimes and foliar sprays of potassium on growth and economics of summer greengram (Vigna radiata) - SONAL ATHNERE*; AVINASH KOLAGE; YOGINI GAGARE; MAHESH GADAKH (Indian Journal of Agronomy, 2001)
An agronomic investigation was carried out at Rahuri, Maharashtra, India during summer 2018, to study the ef- fect of irrigation schedule and foliar application of potash on growth, yield and quality of summer greengram [Vigna radiata (L.) R. Wilczek]. The experiment was laid out in a split-plot design with 3 replications. The experiment con- sists of 12 treatments involving 4 main-plot treatments, i.e. irrigation schedules at 40, 60, 80 and at 100 mm CPE and the subplot treatments are foliar application of 1% potash (KNO ) at flowering, at pod-development stage and 3 at flowering and pod-development stage. Scheduling of irrigation at 40 mm CPE recorded significantly higher growth attributes like plant height, number of leaves, leaf area, plant spread, number of branches, dry matter and seed yield of summer greengram (13.31 q/ha) at harvesting and it was at par with treatment irrigation at 60 mm CPE (13.08 q/ha). Foliar application of 1% potash (KNO ) at flowering and at pod development stage resulted in 3 significantly higher growth attributes and seed yield of summer green gram (12.42 q/ha). Among the different irri- gation schedules, treatment irrigation at 40 mm CPE resulted in the maximum gross monetary returns (`67,560/ ha), net monetary returns (`33,705/ha) and benefit: cost (B : C) ratio (1.99) and it was at par with treatment irriga- tion at 60 mm CPE having net monetary returns (`31,358/ha) and B:C ratio (1.99). The foliar application of 1% pot- ash (KNO ) at flowering and at pod development stage recorded significantly higher gross monetary returns 3 (`62,651/ha), net monetary returns (`30,917/ha), and B : C ratio (1.97). Irrigation at 60 mm CPE and foliar applica- tion of 1% potash at flowering and pod-development stage to summer greengram found suitable preposition to achieve the highest grain yield as well as net monetary returns